Biosynthesis and Characterization of Vosoritide by Escherichia coli - Huang, Shuaiyi; Hu, Xiaoyue; Luo, Tao; Xu, Jun; Duan, Yu; Lu, Jianguang; Feng, Jun (Pharmaceutical Fronts, 2025)
Vosoritide is a therapeutic peptide that promotes skeletal growth by targeting the NPR-B receptor and was approved in 2021 for the treatment of achondroplasia. However, its high production cost poses a considerable economic burden on patients, limiting its widespread use. This study aims to establish an efficient and cost-effective biosynthetic process for the production of Vosoritide using Escherichia coli. In this work, Vosoritide was expressed as inclusion bodies (IBs) in E. coli BL21 (DE3) via a gp55 fusion strategy. Downstream processes, including fermentation, HCl-induced acidic cleavage of IBs, pH-dependent protein precipitation, as well as the performing conditions of the ion-exchange chromatography and reverse-phase chromatography, were optimized. The analysis methods included sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), high-performance liquid chromatography (HPLC), and liquid chromatography-tandem mass spectrometry. Cyclic guanosine monophosphate (cGMP) assays were conducted to assess the biological activity of the protein in NIH3T3 cells. Vosoritide was obtained at 1.3 g per liter of fermentation broth with a purity exceeding 99%. The peptide's primary structure, molecular weight, and disulfide bond integrity were also confirmed through mass spectrometry and peptide mapping. The purified Vosoritide stimulated cGMP production in NIH3T3 cells with a half-maximal effective concentration (EC50) of 0.37 nmol/L. In conclusion, this study provided a scalable, high-yield production method for Vosoritide that yields Vosoritide with pharmaceutical-grade purity and activity, holding significant potential for manufacturing a cost-effective biosimilar with broader clinical accessibility.
Keywords: Vosoritide; achondroplasia (ACH); biosimilars; inclusion bodies